2024
DOI: 10.16930/2237-7662/rccc.v12n36p38-52
|View full text |Cite
|
Sign up to set email alerts
|

Análise Discriminante como Preditiva de Dificuldades Financeiras em Empresas Brasileiras do Mercado Acionário

Abstract: Verificar a situação econômico-financeira de uma empresa pressupõe a análise conjunta de suas demonstrações contábeis, no intuito de prever as condições futuras de gerar resultados e de honrar seus compromissos. O presente artigo tem como objetivo estimar funções discriminantes para os grupos de empresas lucrativas, intermediárias e deficitárias, listadas na BM&FBOVESPA, no período de 2009 a 2011. Os procedimentos metodológicos utilizados caracterizam o estudo como pesquisa descritiva, documental e quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
2
5
0
2
Order By: Relevance
“…For this reason, the option was made to focus only on its results. This level of accuracy was very close to the estimates of the discriminant function reported in Teixeira et al (2013), who had an accuracy level of 82.8%. Table 7 shows the estimates of the coefficients of Equation ( 38), as well as the degree of importance of each variable in this equation.…”
Section: Discriminant Functions Estimatessupporting
confidence: 86%
See 4 more Smart Citations
“…For this reason, the option was made to focus only on its results. This level of accuracy was very close to the estimates of the discriminant function reported in Teixeira et al (2013), who had an accuracy level of 82.8%. Table 7 shows the estimates of the coefficients of Equation ( 38), as well as the degree of importance of each variable in this equation.…”
Section: Discriminant Functions Estimatessupporting
confidence: 86%
“…The gold price, volume trading exchange, average purchase and sale of the exchange rate and monthly deposit were used as indicators. Finally, they reported that ANN was able to adequately predict, with 95% of correct answers, the income of the sampled companies Teixeira et al (2013) aimed to use the DA method in the estimation of functions to discriminate companies between profitable, intermediary and non-profitable companies, between 2009 and 2011. Variables used were liquidity (general, current and dry), turnover asset, assets return, net margin, equity return, indebtedness, debt composition and fixed assets.…”
Section: Literature Referencesmentioning
confidence: 99%
See 3 more Smart Citations